The Epigravettian chronology and the human population of eastern Central Europe during MIS2. (1st November 2021) - Lengyel, György; Bárány, Annamária; Béres, Sándor; Cserpák, Ferenc; Gasparik, Mihály; Major, István; Molnár, Mihály; Nadachowski, Adam; Nemergut, Adrián; Svoboda, Jiří; Verpoorte, Alexander; Wojtal, Piotr; et al.
Abstract: The goal of this paper is to refine the relative and absolute chronology of Epigravettian culture (26.5–15.0 ka) in eastern Central Europe (ECE) and clarify its relation to the Last Glacial Maximum (LGM) and subsequent climatic changes. Epigravettian sites were sorted into three chronological clusters: initial LGM (ILGM) (26.5–24.0 ka), local LGM (LLGM) (24.0–20.0 ka), and post-LGM (PLGM) (20.0–14.7 ka). We obtained new radiocarbon dates from previously dated and undated sites, then analysed the lithic tool typology and faunal data to seek correlations between age and archaeological features. The lithic typology study did not find differences between ILGM and LLGM sites, but the tool type variance between LLGM and PLGM was significant, applicable for relative chronology. ILGM and LLGM lithic assemblages were characterized by domestic tool dominance and the frequent use of flake tools. PLGM assemblages were correlated with armature dominance and blade/let tools. Among the armatures, backed point variants characterized the PLGM sites compared to the ILGM and LLGM. The sole ILGM lithic armature was the retouched blade/let point. The LLGM also possessed this type and often included backed blade/lets. ILGM faunal data, although few, implied the hunting of mammoth and reindeer. The LLGM data represented recurring hunting of reindeer and horse, and PLGM data indicated the hunting of horse, reindeer, and mammoth. Our results suggested that the territory of Poland was deserted by humans in the LLGM. Moravia and Lower Austria was inhabited until the first half of the LLGM, while the Carpathian Basin was all along the ILGM. The preference for the Carpathian Basin could have been the milder climate, the abundance of fauna, and permanent access to tree vegetation. After the LGM the glacial flora and fauna gradually disappeared, leading to a reduced human presence in southern ECE. Thus, the disappearance of the Epigravettian culture and Pleistocene hunter-gatherer occupations are linked to the amelioration of climate that resulted in the disappearance of the Pleistocene environment. Highlights: Our data refined the absolute and relative chronologies of the Epigravettian. Relative chronological keys are lithic armature and faunal evidence. There was a lack of human population in Poland throughout the LGM. The Carpathian Basin was the most densely populated territory in ECE during the LGM. The withdraw of Pleistocene environment led to the disappearance of the Epigravettian.